Triterpenoids with Cytotoxic Potential from the Leaves of Tridax procumbens L. - Vaishali Rai,; Vinitha Ramanath Pai,; Surya Ram Duwal, (International Journal of Phytomedicine, 2017)
The anticancer activity of crude extracts of the leaves of Tridax procumbens, against two breast cancer cell lines-MCF-7 (benign) and MDA-MB-231 (metastatic) were investigated and an attempt was made to identify the anticancer principle. The extracts with methanol (TPM), ethanol (TPE) and chloroform (TPC) as solvents were screened for cytotoxicity by MTT assay against MCF-7 cells. The effective extract was further evaluated on MDA-MB-231 cells. Among the three extracts, TPC was effective at an IC50 value of 136 µg/ml and 129 µg/ml on MCF-7 and MDA-MB-231 cells respectively. Phytochemical analysis of the extract showed the presence of only steroids and terpenoids and their concentration was high (77.4% w/w). HPLC-MS of the chloroform soluble crude extract revealed a major peak (57.59% concentration) at a retention time of 4.78 min and MS data of this peak revealed presence of two fragments of molecular weight 475.80 and 701.80. The compounds were identified to be 3β, 9β-Dihydroxy-18α-oleanan-28-oic acid, a derivative of oleanolic acid and 3β, 28-Bis (cinnamoyl) betulin respectively, both from the triterpenoid family.